Not All Acute Abdomen Cases in Early Pregnancy Are Ectopic; Expect the Unexpected: Renal Angiomyolipoma Causing Massive Retroperitoneal Haemorrhage - Muhammad Asim Rana; Ahmed F. Mady; Nagesh Jakaraddi; Shahzad A. Mumtaz; Habib Ahmad; Kamal Naser (Case Reports in Critical Care)
Retroperitoneal haemorrhage (or retroperitoneal haematoma) refers to an accumulation of blood found in the retroperitoneal space. It is a rare clinical entity with variable aetiology including anticoagulation, ruptured aortic aneurysm, acute pancreatitis, malignancy, and bleeding from renal aneurysm. Diagnosis of retroperitoneal bleed is sometimes missed or delayed as presentation is often nonspecific. Multislice CT and arteriography are important for diagnosis. There is no consensus about the best management plan for patients with retroperitoneal haematoma. Stable patients can be managed with fluid resuscitation, correction of coagulopathy if any, and blood transfusion. Endovascular options involving selective intra-arterial embolisation or stent-grafts are clearly getting more and more popularity. Open repair is usually reserved for cases when there is failure of conservative or endovascular measures to control the bleeding or expertise is unavailable and in cases where the patient is unstable. Mortality of patients with retroperitoneal haematoma remains high if appropriate and timely measures are not taken. Haemorrhage from a benign renal tumour is a rarer entity which is described in this case report which emphasizes that physicians should have a wide index of suspicion when dealing with patients presenting with significant groin, flank, abdominal, or back pain, or haemodynamic instability of unclear cause. Our patient presented with features of acute abdomen and, being pregnant, was thought of having a ruptured ectopic pregnancy.